The physics principle of the generation of flow configuration - Miguel, Antonio F (2012)
Design – configuration, architecture, shape, structure, pattern, rhythm – is omnipresent in nature [1–4]. The vast majority of natural systems are non-equilibrium thermodynamic systems, containing internal flows (e.g., mass, heat, charges, goods, etc.) with a defined configuration. The first law of thermodynamics states that energy is conserved in these systems as it flows through them [5], while the second law determines that the entropy outflow must be greater than the entropy inflow. The constructal law [5] complements the other two by stating that, for a system to persist, configuration must morph (evolve) towards designs that make it easier for currents to flow. This last self-standing law of design indicates that the acquisition of configuration is a dynamic process that guides and facilitates flowing.